Potential Rhizopus spp. in control the growth of Aspergillus flavus FNCC6109 in broiler chicken concentrate feed - Jagat, Lalu Muhammad Sakti Surya; Darmayasa, Ida Bagus Gede; Wijana, I Made Sara (Jurnal Biologi Udayana; Vol 25 No 2 (2021): JURNAL BIOLOGI UDAYANADO - 10.24843/JBIOUNUD.2021.v25.i02.p06, 2021)
Aspergillus flavus contamination of agriculture in Indonesia can cause problems to animal health and productivity. Some factors can support the appearance of contamination in feed, especially temperature and humidity. The main objective of this research was to investigate potency of Rhizopus spp. on inhibit A. flavus FNCC6109 in broiler chicken concentrate feed. The experiments were conducted dual culture method and the inhibition test of the Rhizopus spp. filtrate culture was incubated for 3, 4 and 5 days on in vitro. The in vivo test was directly applied in broiler chicken concentrate feed which added Rhizopus spp. filtrate culture concentration at 10% (v/v), 20% (v/v), 30% (v/v), 40% (v/v), dan 50% (v/v). The results showed that the Rhizopus spp. filtrate culture significantly (P?0,05) to inhibit the growth of A. flavus FNCC6109 both in vitro and in vivo. The percentage inhibition of Rhizopus spp. filtrate culture incubated for 5 days showed 67,47±2,10% relatively better results than 3 and 4 days, and therefore was used in the in vivo. Application of 50% (v/v) Rhizopus spp. filtrate culture to the broiler chicken concentrate feed significantly reduced 82% population of A. flavus FNCC6109 after 15 days incubated relative to that of negative control (concentrate feed without addition Rhizopus spp. filtrate culture and A. flavus FNCC6109).